TiN, TiAlN ve AlTiN kaplamaların aşınma performanslarının incelenmesi ve farklı altlık malzemede TiN kaplamanın etkisinin araştırılması - Bozkurt, Tarık (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2006)
Kesici takımların performanslarını artırmak için farklı özelliklere sahipkaplamalar yapılmaktadır. Kaplama türü kesici takımın çalışma koşullarına göreseçilir. TiN, TiAlN ve AlTiN kaplamaları da kesici takımların aşınma dirençleriniartırarak, takım ömrünü uzatır ve daha yüksek hızlarda çalışmasını sağlar. Bu tezçalışmasında TiN, TiAlN ve AlTiN kaplamaların aynı özelliklere sahip altlıkmalzemede aşınma performansları karşılaştırılmıştır. Ayrıca farklı özelliklere sahipaltlık malzemelerde TiN kaplamanın aşınma performansı da incelenmiştir. Aşınmadeneylerinin sonuçları irdelendiğinde farklı özelliklere sahip altlık malzemelerekaplanan TiN kaplamaların aşınma özelliklerinin aynı olduğu yani kaplamaperformansının altlık malzemeden bağımsız olduğu tespit edilmiştir. Elde edilendiğer sonuç ise; aynı özelliklere sahip altlık malzemeye kaplanan TiN kaplamanınaşınma performansının AlTiN kaplamanın aşınma performansından daha yüksekolduğu, AlTiN kaplamanın aşınma performansının da TiAlN kaplamanın aşınmaperformansından yüksek olduğudur.

In order to increase the performance of cutting tools different surface coatingsare devised. The kind of surface coating is chosen according to the operationconditions of the cutting tools. In the same way TiN, TiAlN and AlTiN coatingsincrease the lifetime of the cutting tools and enable them to operate of higher speedby increasing the wear resistance levels of the cutting tools. In this study the wearresistance performances of the TiN, TiAlN and AlTiN surface coatings applied to thesame substract material have been compared. Also, the wear resistance performanceof TiN coating applied to the different substract materials has beenexamined. Results show that the TiN coatings applied to the different substractmaterials have the same performances. That is, the coating performance is notdependent on the substract material. Another result obtained during the experimentsis that the wear resistance of the TiN is higher than the wear resistance of the AlTiN,whereas the wear resistance of AlTiN coating is higher than the wear resistance ofthe TiAlN coating.
Investigation of the wear performance of, TiN, TiAlN and AlTiN coatings and the effect of the TiN coatings on different substract materials
Keywords: Mühendislik Bilimleri; Engineering Sciences